Description of a new species of Dascillus Latreille from Henan, China (Coleoptera: Dascillidae) - Fang, Yan; Yan, Yijie; Jin, Zhenyu (Zootaxa, 2020)
Dascillus Latreille, 1797 (Coleoptera: Dascillidae) currently contains about 40 species, of which 32 have been reported from China (Jin et al. 2013, 2018; Hájek 2016; Terzani et al. 2017; Wang et al. 2019). The Baotianman National Nature Reserve of Henan (33°20ʹ–33°36ʹN, 111°47ʹ–112°04ʹE) which is one of the “world biosphere reserves” recognized by United Nations Educational, Scientific and Cultural Organization for their high ecosystem and species diversity (Zhu et al. 2002). While examining specimens collected from the survey of the Baotianman National Nature Reserve in 2017, conducted by the Hunan Agricultural University (Changsha, China), a new species of Dascillus was identified and is described in this paper.